Stream solute tracer timescales changing with discharge and reach length confound process interpretation. Issue 4 (29th April 2016) - Schmadel, Noah M.; Ward, Adam S.; Kurz, Marie J.; Fleckenstein, Jan H.; Zarnetske, Jay P.; Hannah, David M.; Blume, Theresa; Vieweg, Michael; Blaen, Phillip J.; Schmidt, Christian; Knapp, Julia L.A.; Klaar, Megan J.; et al.
Abstract: Improved understanding of stream solute transport requires meaningful comparison of processes across a wide range of discharge conditions and spatial scales. At reach scales where solute tracer tests are commonly used to assess transport behavior, such comparison is still confounded due to the challenge of separating dispersive and transient storage processes from the influence of the advective timescale that varies with discharge and reach length. To better resolve interpretation of these processes from field‐based tracer observations, we conducted recurrent conservative solute tracer tests along a 1 km study reach during a storm discharge period and further discretized the study reach into six segments of similar length but different channel morphologies. The resulting suite of data, spanning an order of magnitude in advective timescales, enabled us to (1) characterize relationships between tracer response and discharge in individual segments and (2) determine how combining the segments into longer reaches influences interpretation of dispersion and transient storage from tracer tests. We found that the advective timescale was the primary control on the shape of the observed tracer response. Most segments responded similarly to discharge, implying that the influence of morphologic heterogeneity was muted relative to advection. Comparison of tracer data across combined segments demonstrated that increased advective timescales could be misinterpreted as a change in dispersion or transient storage. Taken together, our results stress the importance of characterizing the influence of changing advective timescales on solute tracer responses before such reach‐scale observations can be used to infer solute transport at larger network scales. Key Points: Advection is the primary control on observed stream solute tracer responses The influence of spatial heterogeneity in morphology is muted by advection Interpretation of solute transport requires consideration of tracer timescales